Experiences of Upper Limb Somatosensory Retraining in Persons With Stroke: An Interpretative Phenomenological Analysis - Turville, Megan L.; Walker, Johanne; Blennerhassett, Jannette M.; Carey, Leeanne M. (Frontiers in Neuroscience, 2019)
Purpose: The aim of this study was to explore experiences of upper limb somatosensory discrimination retraining in persons with stroke. Methods: A qualitative methodology was used within the context of a randomised control trial of somatosensory retraining: the CoNNECT trial. Participants in the CoNNECT trial completed a treatment program, known as SENSe therapy, to retrain upper limb somatosensory discrimination and recognition skills, and use of these skills in personally valued activities. Eight participants were interviewed on their experience of this therapy. Data were analysed using Interpretative Phenomenological Analysis (IPA). Results: Five themes represented participants’ experiences of upper limb somatosensory retraining after stroke: (1) loss of sensation and desire to reclaim normality; (2) harnessing positivity in the therapeutic relationship and specialised therapy; (3) facing cognitive and emotional challenges; (4) distinct awareness of gains and differences in bodily sensations; and (5) improved functioning: control and choice in daily performance. Persons with stroke experienced somatosensory retraining as a valuable treatment that provided them with sensory and functional gains. Conclusion: Upper limb somatosensory retraining is a treatment that persons with stroke perceived as challenging and rewarding. People who have experience stroke believed that somatosensory retraining therapy assisted them to improve their sensation, functional arm use, as well as daily performance and participation in life.